Enhancing food security through halal system with a logistic regression analysis - Tribowo Rachmat Fauzan; Ajeung Syilva Syara (Enrichment : Journal of Management, 2023)
This study aims to analyze the level of food security, factors which affect the level of food security and efforts to increase it level of food security with logistic regression analysis.Food security is clearly essential for the continued lifestyles of the human race. Food this is safe, secure, and sustainable to eat is a proper that belongs to each person on our planet and need to not be denied to absolutely everyone, anywhere in the globe, consisting of Indonesia. When it involves resolving troubles with the provision of food for its human beings, Indonesia, as the united states with largest Muslim population, need to additionally consider the halal detail. The usage of halal is fine no longer simplest for individual needs, but additionally for the purposes of society as a whole. The intention of this studies is to test the impact that halal concerns have on food safety in Indonesia. The Binary Logit Model became utilised if you want to do research oresearchn the halal meals security machine in Indonesia. We used food safety factors based on Jonsson and Toole which will determine the food protection level of Indonesia, which served as the structured variable. According to the findings of this reserach, the quantity of halal consciousness and halal certification in Indonesia has significant affects at the united states of america's standard level of food protection. The outcomes suggest that food protection might be completed now not just by using growing the satisfactory and quantity of intake, but additionally through incorporating Islamic viewpoints as an extra supply to save you food insecurity. This would be the first-class way to obtain food protection